Attention Modulates the Ensemble Coding of Facial Expressions. (April 2022) - Ying, Haojiang
Ensemble coding and attention are two mechanisms utilized by our visual system to overcome the limitation of visual processing when confronted with the overwhelming visual information. Recent evidence in ensemble coding of size suggests that the attended items contributed more to the averaging. On the other hand, some new evidence also indicates that reduced attention jeopardies the perceptual averaging of stimuli. What is the relationship between attention and ensemble coding? To answer this question, in the current study, we tested whether an exogenous attentional cue would influence the reported mean emotion of a crowd. We showed participants a group of four faces with different emotions. Participants' attention was guided to the happiest or saddest face (attention conditions), or not to any specific face (baseline condition). The results supported the notion that the attention alters the ensemble perception of the facial expression by elevating the weight of that face in the ensemble representation. This opens the question for the neural mechanisms of ensemble coding and its connection to visual attention.